UJI KUALITAS MUTU PINDANG CUE-BESEK IKAN LAYANG(Decapterus sp.) DI DESA JANGKAR KABUPATEN SITUBONDO - Ika Junianingsih (Samakia : Jurnal Ilmu Perikanan, 2015)
The fish in fresh form is perishable and rot (Perishable Food) that required the processing of fresh fish in order to save power more durable, more easily distributed from production centers to consumption centers, as well as more easily consumed. Cue Pindang traditional processing carried out by the fishing community Village Anchor Situbondo is the processing of fresh fish traditionally preserved by salting combination process and boiling (heating) at high temperatures and a relatively short time using Besek container. The traditional processing business must pay attention to the quality of processed products because the quality of the processed product quality will affect the sale price. Good quality or high in refined products will have an impact on fish prices higher. This study was conducted to determine and analyze the quality of boiled fish quality kite with pemindangan methods cue-baskets. The research was conducted from August to October 2014, with research sites in the Village Anchor, Situbondo. Stages of research conducted through sampling, sample preparation, followed by laboratory tests at the Faculty of Food Technology, University of Brawijaya. Chemical testing methods performed through proximate analysis (% wet weight) include; moisture content, ash content, protein content, carbohydrate, fat and mineral levels based standard proximate analysis. The results showed that the test value proximate boiled fish for carbohydrate content of 0.99%, 27.00% protein content, fat content 3.80%, mineral content 2:26% moisture content and ash content of 64.45% by 1:50%. The chemical composition of boiled fish float indicates that the quality of the quality of the product in accordance with the standards specified quality requirements and safe for the general public.